(untitled) (Research, Society and Development, 2022)
Introduction: The process of memory occurs through phases due to various stimuli. Sound is an important source of such stimulation. Extinction, with which previously established information is suppressed, represents a new learning process. Objective: To investigate the interference of Mozart’s Sonata K448 in the extinction of the memory of fear of the sound. Methods: C57BL/6J mice were used, divided into: G1: Mozart (n=7); G2: Environment (n=6); and G3: Control (n=6). Only the G1 group was exposed to music from intrauterine life onwards. On days 50 to 53 after birth, the animals were subjected to Habituation. On the 54th day, an Aversive Training was performed only with G1 and G2. On the 55th day, the Extinction Test started, lasting twelve consecutive days with the three groups. On the 81st day, all groups passed the Recall Test. The tests were videotaped for analysis. Data were analyzed using the repeated measures ANOVA test, with p≤0.05 being considered significant. Results: There was no groups main effect (F(2;16)=2,70; p=0,098), nor an interaction between groups x days (F(2,16;17,30)=1,58; p=0,147). Conclusion: Although no statistically significant difference was observed between the groups, future studies with larger samples may be opportune to better elucidate the influence of music on memory.